Surgical techniques and function outcome for cingulate gyrus glioma, how we do it - Gong, Fangyuan; Jin, Lei; Song, Qiuwei; Yang, Zhong; Chen, Hong; Wu, Jinsong (Frontiers in Oncology, 2022)
OBJECTIVE Cingulate cortex and cingulum both play crucial roles in limbic system. The aim of study is to observe and analyze surgical outcomes of cingulate gyrus glioma through extents of resection (EORs), overall survival (OS), and postsurgical neurological outcome. METHODS The authors retrospectively studied 95 consecutive adult cases of primary cingulate gliomas that all underwent craniotomies and tumor resection. The patients were classified into unitary sub-region based on the four-division model. The information of clinical symptoms, pathology, EOR, postoperative neurological outcome and survival were analyzed through group comparison. RESULTS Low-grade gliomas (LGGs) were more prevalent (69.47%) for cingulate gyrus. Diffuse astrocytoma (40.00%) was most common histopathological diagnosis in total. Regarding sub-regions tumor involved in, midcingulate cortex (MCC) glioma was most prevalent (54.74%) followed by anterior cingulate cortex (ACC) glioma. Among all patients, 83 patients (87.37%) received EOR ≥ 90%. In LGG group, 58 patients (87.88%) received EOR ≥ 90%. The achievement of EOR significantly correlated with survival (P = 0.006). MCC cases were significantly associated with short-term morbidity in either language or motor function (P = 0.02). Majority of ACC cases (80.65%) escaped from any short-term deficits and nearly 90% free for permanent morbidity. Tumors in the dominant hemisphere were significantly associated with language dysfunction or cognition dysfunction, either short-term (P=0.0006) or long-term morbidity (P=0.0111). Age was the only postoperative susceptible predictor for all types of transient (P=0.021) and permanent (P=0.02) neurological deficit. CONCLUSIONS Regarding cingulate gyrus glioma, the management of surgical plans could be carried out into four sub-region level. In spite of short-term neurological dysfunction caused by surgical procedure, majority of transient dysfunction could be relieved or recovered in long-term. The necessary effort to prolong overall survival is still to achieve advisable EOR.